Ethiopia : Fourth Review and Third Annual Program Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Requests for Extension of Arrangement and for Additional Interim Assistance Under the Enhanced HIPC Initiative. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
Recent economic developments have been adversely affected by the severe drought. The mission and the authorities updated the macroeconomic framework for 2003/04 and the medium-term in light of recent developments and the latest World Economic Outlook (WEO) price projections. The fiscal strategy is focused on achieving and maintaining public debt sustainability, and maximizing the efficient use of highly concessional resources for poverty reduction-related activities. The policies to be implemented under the third annual program aim at maintaining macroeconomic stability and achieving rates of economic growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet